Effects of extraction conditions on the antioxidant activity of phanerochaete chrysosporium bioactive phenolics - Chen Hui Wen (School of Bioprosess Engineering, University Malaysia Perlis, 2012)
Phanerochaete chrysosporium or know as white rot fungus has the major ability in lignin-degradable. however, antioxidant activities of the extracts from phanerochaete chrysosporium biomass are poorly reported. In this study, the extraction conditions for antioxidant activity of phanerochaete chrysosporium biomass extracts were determined by using plackett-Burman experimental design. The extraction conditions studied were solid-solvent ratio, solvent concentration, agitation speed, extraction pH, temperature, and time. positive effect variables such as solid -solvent ratio, pH, and time were found to be 24.19, 23.57 and 2.82 respectively. on contry , agitation speed, solvent concentration and temperature had negatively effect on antioxidant activity at -0.45, -13.73 and - 18.42 respectively.